2017
DOI: 10.1371/journal.pone.0180449
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of HY5/HYH expression in Arabidopsis reveals a root-autonomous HY5-mediated photomorphogenic pathway

Abstract: ELONGATED HYPOCOTYL 5 (HY5), a member of the bZIP gene family, is a positive regulator of the light signaling pathway in Arabidopsis thaliana. Whereas the hy5 mutant exhibits an elongated hypocotyl when grown in the light, the hy5 homolog (hyh) mutant does not. Although the functions of HY5 and HYH in light-mediated seedling development have been revealed, the tissue-specific expression patterns of HY5 and HYH and their interconnected regulation are largely unknown. Here, we report that HY5 regulates HYH expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 45 publications
2
33
1
Order By: Relevance
“…Given that HY5 has the potential to regulate STOM expression we next examined expression of HY5 using confocal microscopy to study the localisation of HY5:CFP in HY5proHY5: CFP transgenic plants. It should be noted that previous studies have shown that HY5 is expressed widely throughout the plant including leaf tissue and that HY5 protein is mobile, therefore this already indicates that HY5 has the potential to regulate STOM expression in the mesophyll [32,33]. Our analysis confirmed the results of previous studies and HY5:CFP signal was clearly detected in the epidermis and stomatal lineage cells as well as the mesophyll ( Fig 1C and 1D).…”
Section: Resultssupporting
confidence: 91%
“…Given that HY5 has the potential to regulate STOM expression we next examined expression of HY5 using confocal microscopy to study the localisation of HY5:CFP in HY5proHY5: CFP transgenic plants. It should be noted that previous studies have shown that HY5 is expressed widely throughout the plant including leaf tissue and that HY5 protein is mobile, therefore this already indicates that HY5 has the potential to regulate STOM expression in the mesophyll [32,33]. Our analysis confirmed the results of previous studies and HY5:CFP signal was clearly detected in the epidermis and stomatal lineage cells as well as the mesophyll ( Fig 1C and 1D).…”
Section: Resultssupporting
confidence: 91%
“…Since HY5-GFP was shown to be mobile despite the increased size of the HY5-GFP protein compared with HY5 itself, we expect that HY5-YFP (38 kD) can also be mobile via the phloem. HY5 can induce transcription of its own gene in the root (Supplemental Figure 3); thus, an increase in HY5 protein can lead to an increase in HY5 expression (Lee et al, 2007;Binkert et al, 2014;Campos et al, 2016;Zhang et al, 2017). It is possible that HY5 unloaded at the root tip remains in the cells close to where LRPs are initiated and then upregulates their own expression, leading to increased HY5 in the LRP.…”
Section: Discussionmentioning
confidence: 99%
“…The role for HY5 in Arabidopsis root development has been known for a long time, as HY5-deficient mutants show defects in root hair development, gravitropism, lateral root outgrowth, and elongation (Oyama et al, 1997;Sibout et al, 2006). The HY5 protein is, as was discovered recently, translocated via the phloem toward the root, with root-specific HY5 and HYH transcription, and promoted root development as a consequence (Chen et al, 2016;Zhang et al, 2017; Fig. 3D).…”
Section: The Rootsmentioning
confidence: 93%